Position statement—altitude training for improving team-sport players' performance: current knowledge and unresolved issues. (26th November 2013) - Girard, Olivier; Amann, Markus; Aughey, Robert; Billaut, François; Bishop, David J; Bourdon, Pitre; Buchheit, Martin; Chapman, Robert; D'Hooghe, Michel; Garvican-Lewis, Laura A; Gore, Christopher J; Millet, Grégoire P; et al.
Abstract : Despite the limited research on the effects of altitude (or hypoxic) training interventions on team-sport performance, players from all around the world engaged in these sports are now using altitude training more than ever before. In March 2013, an Altitude Training and Team Sports conference was held in Doha, Qatar, to establish a forum of research and practical insights into this rapidly growing field. A round-table meeting in which the panellists engaged in focused discussions concluded this conference. This has resulted in the present position statement, designed to highlight some key issues raised during the debates and to integrate the ideas into a shared conceptual framework. The present signposting document has been developed for use by support teams (coaches, performance scientists, physicians, strength and conditioning staff) and other professionals who have an interest in the practical application of altitude training for team sports. After more than four decades of research, there is still no consensus on the optimal strategies to elicit the best results from altitude training in a team-sport population. However, there are some recommended strategies discussed in this position statement to adopt for improving the acclimatisation process when training/competing at altitude and for potentially enhancing sea-level performance. It is our hope that this information will be intriguing, balanced and, more importantly, stimulating to the point that it promotes constructive discussion and serves as a guide for future research aimed at advancing the bourgeoning body of knowledge in the area of altitude training for team sports.